Lestodelphys halli EN LA PROVINCIA DE SANTA CRUZ (ARGENTINA): PRIMER HALLAZGO EN UN SITIO ARQUEOLÓGICO EN LA COSTA PATAGÓNICA Lestodelphys halli IN THE PROVINCE OF SANTA CRUZ (ARGENTINA): FIRST FINDING IN AN ARCHAEOLOGICAL SITE IN COAST PATAGÓNICA - MIGUEL A ZUBIMENDI; SERGIO BOGAN (Magallania, 2006)
En esta nota nos proponemos tres objetivos. Primero, dar a conocer la presencia de Lestodelphys halli (Thomas 1921) en un sitio de la localidad arqueológica de Punta Medanosa, Provincia de Santa Cruz (Argentina). Segundo, realizar una breve caracterización de la especie, así como una descripción de los rasgos osteológicos de interés para su determinación en otros contextos arqueológicos. Tercero, realizar un repaso bibliográﬁco de sitios en los cuales se ha registrado la presencia de L. halli en la Republica Argentina In this paper we have proposed three main objectives: ﬁrst, to inform the presence of Lestodelphys halli (Thomas 1921) in a site in the archaeological locality of Punta Medanosa, Santa Cruz province (Argentina). Second, to make a brief characterization of the biology, distribution, etc. of this taxon, and a description of osteological characters of interest for archaeological context. Third, to make a systematic description of the presence of L. halli in archaeological sites in the Argentine Republic, with an emphasis on the kind of information given in each case